Proyecto de inversión para la creación de una empresa de lavado en seco y tintorería en la ciudad de Loja - Camacho Soto, Silvana del Cisne (2016)
The research paper entitled "INVESTMENT PROJECT FOR THE CREATION OF A COMPANY dry cleaning and dry cleaning Loja", the same that was met with the development of specific objectives: to determine market research, conducting the technical study develop the legal study - administrative, make economic and financial study to evaluate the feasibility of implementing the company. To carry out this research was necessary to start with a market study in which 397 surveys were applied to the inhabitants of the four urban parishes in the city of Loja, achieving determine supply and unmet demand that exists in the town which is 5422 potential users of suits, dresses 4093, 5744 sweaters and quilts of 5617 that require this service to meet your needs. With the development of the technical study the functioning and operation of the project was defined as: size, location of the company, the same that will be located in the San Sebastian parish in the streets Manuel Agustín Aguirre and Lourdes, providing a suitable working environment for staff efficiency and thus provide a quality service. The company will work in the first year with 80% of its installed capacity. This study also includes the flow chart of the process of dry cleaning of garments. 6 In terms of organizational structure will count on the participation of 4 persons: Owner, Operator, Ironing, Receptionist; also a Manual of functions for different positions. In which states that the company is established as sole proprietorship and the respective steps for operating permits starting with getting the RUC in the Internal Revenue Service is made. Through economic study found that implementation of this company deserves an investment of $ 36,232.45 comprising working capital, of which 17% will be financed with equity and 83% through a loan from the Corporation National financial; and whose capital recovery period will be invested in one year, one month and twenty four days. For the first year it is planned to wash clothes 13680, thus demonstrating that in the first year of the project a net profit for the year of $ 17,422.24 will be obtained. . Finally in the financial evaluation of various financial indicators allowed to establish the feasibility of the project as they are analyzed: Net Present Value of $ 58,813.28; Internal Rate of Return of 68.67%; Benefit Cost Ratio and $ 1.42; Sensitivity analysis with increased costs of 12.39% with a sensitivity of 0.99%; and a decrease in income of 8.71%; the same that demonstrate the feasibility of the project to implement the company dry cleaning. 7 Consequently this proposal is considered feasible if implemented, by the results of the market study and financial study indicate that the company may be created that would generate the same returns on investment around, creating value for its owner and moreover contribute to social and economic development of the city of Loja